1998
DOI: 10.3171/jns.1998.88.6.1058
|View full text |Cite
|
Sign up to set email alerts
|

Early metabolic alterations in edematous perihematomal brain regions following experimental intracerebral hemorrhage

Abstract: These results, which demonstrate normal to increased high-energy phosphate and carbohydrate substrate concentrations in edematous perihematomal regions during the early hours following ICH, are qualitatively similar to findings in other brain injury models in which a reduction in metabolic rate develops. Because an energy deficit is not present, lactate accumulation in edematous white matter is not caused by stimulated anaerobic glycolysis. Instead, because glutamate concentrations in the blood entering the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 41 publications
1
65
0
2
Order By: Relevance
“…Both vasogenic and cytotoxic edema lead to disruption of the blood-brain barrier, sodium-pump failure, and neuronal death. 42 Controversy exists as to whether there are areas of ischemic tissue at risk around an ICH analogous to an ischemic penumbra. There is direct experimental evidence of ischemic tissue surrounding the hematoma, 43,44 and radiologic support is also available.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Both vasogenic and cytotoxic edema lead to disruption of the blood-brain barrier, sodium-pump failure, and neuronal death. 42 Controversy exists as to whether there are areas of ischemic tissue at risk around an ICH analogous to an ischemic penumbra. There is direct experimental evidence of ischemic tissue surrounding the hematoma, 43,44 and radiologic support is also available.…”
Section: Pathophysiologymentioning
confidence: 99%
“…As in traumatic brain injury, early removal of the hematoma and cellular debris, either by surgical removal of the clot or by the action of the inflammatory cells such as microglia and macrophages, help to reduce the extent of secondary damage [27,28]. Animal studies have shown that perihematoma edema can be divided into three phases: immediate (up to 24 h after hemorrhage), intermediate (from 24 h to 5 days), and late (beyond 5 days) [29]. The immediate edema results from osmotically active proteins accumulating in the extravascular compartment and can be seen on histological studies, but not on imaging.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Early edema is due to the accumulation of serum proteins of the clot that contains osmotic activity [22]. Subsequently, the presence of cytotoxic and vasogenic edema leads to blood-brain barrier disturbances, sodium pump failure, and ultimately the death of neurons [23,24]. The first hours after ICH onset, the blood-brain barrier continues to be nonpermeable for larger molecules, but after 8 to 12 hours the permeability increases and therefore fosters further edema formation [20].…”
Section: Edemamentioning
confidence: 99%